2014
DOI: 10.5114/noms.2014.44563
|View full text |Cite
|
Sign up to set email alerts
|

Is the depression level the factor influencing the effectiveness of the group weight reduction program?

Abstract: Introduction: The aim of the study was to assess the influence of the depression level on the effects of the group weight reduction program. Material and methods:The study group involved 57 overweight and obese subjects [age 45.9 ± 13.9 years, body mass index (BMI) 35.5 ± 5.4 kg/m 2 ]. All patients participated in a 3-month group weight reduction program. Body mass and height were measured and BMI was calculated, the depression level was assessed using Beck's Depression Inventory (BDI) at baseline and at the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
(32 reference statements)
0
1
1
Order By: Relevance
“…This hypothesis is contradictory to our previously published results, showing that depressive symptoms levels did not influence the effectiveness or the duration of continuation of a obesity treatment program [34][35][36]. The factors responsible for the above phenomena are probably more complex, and not all predictors have been identified yet.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…This hypothesis is contradictory to our previously published results, showing that depressive symptoms levels did not influence the effectiveness or the duration of continuation of a obesity treatment program [34][35][36]. The factors responsible for the above phenomena are probably more complex, and not all predictors have been identified yet.…”
Section: Discussioncontrasting
confidence: 93%
“…Another limitation is cross-sectional design. However, our previously published results shown that the depression level at baseline did not influence the effectiveness of the group weight reduction program [35].…”
Section: Discussionmentioning
confidence: 77%